Lithium iron phosphate positive electrode active material, its preparation method, and lithium-ion battery
Patent Information
- Application Number
- JP2024551660
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-07
- Filing Date
- 2023-02-22
- Publication Date
- 2025-03-26
- Estimated Expiration
- 2043-02-22
Smart Images

Figure 2025508507000001_ABST
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This disclosure claims priority to Chinese Patent Application No. 202210228274.0, filed on March 7, 2022, and entitled “Lithium iron phosphate positive electrode active material, preparation method thereof, positive electrode sheet and lithium ion battery,” the entire contents of which are incorporated herein by reference.
[0002] The present disclosure relates to the field of lithium-ion batteries, and in particular to a lithium iron phosphate positive electrode active material, a method for preparing the same, and a lithium-ion battery. [Background technology]
[0003] Lithium iron phosphate materials are widely used due to their high safety, low cost, environmental compatibility and other advantages. However, lithium iron phosphate materials also have obvious disadvantages. They have a low maximum compressed density (2.1-2.5 g / cm 3 ), which results in a low energy density of the battery prepared with the lithium iron phosphate material, so that the demand for a battery with a long battery life cannot be met. In order to improve the energy density of the battery, lithium iron phosphate materials with high compaction density have become the general development direction in the industry. However, in the lithium iron phosphate materials with high compaction density, the electrochemical performance of the battery is often reduced when the compaction density of lithium is increased. Summary of the Invention [Means for solving the problem]
[0004] In order to solve the above technical problems, the present disclosure provides a lithium iron phosphate positive electrode active material, its preparation method, and a lithium-ion battery. By adjusting the particle size parameters of the two component lithium iron phosphate materials, the positive electrode active material obtained by mixing the two materials in any ratio can be made to have a high compaction density, and the battery prepared therewith has excellent electrochemical performance.
[0005] In particular, in a first aspect, the present disclosure provides a lithium iron phosphate active cathode material. The lithium iron phosphate active cathode material is formed by mixing a first lithium iron phosphate material and a second lithium iron phosphate material. When the volume distribution percentage of the first lithium iron phosphate material reaches a maximum value, the corresponding particle size is D 1 mo μm, 0.3≦D 1 mo When the volume distribution percentage of the second lithium iron phosphate material reaches a maximum value, the corresponding particle size is D 2 mo μm, 1≦D 2 mo ≦5, D 1 mo <D 2 mo The discreteness of the particle size distribution of the first lithium iron phosphate material is A1, and the discreteness of the particle size distribution of the second lithium iron phosphate material is A2, where 1≦A1≦3 and 2≦A2≦4. D 1 mo and A1 is 4.07 <A1×(2.31+D 1 mo )<16. D 2 mo and A2 is -0.4 <A2×(D 2 mo -1.15)<14.
[0006] The maximum compression density of the positive electrode sheet containing the positive electrode active material is 2.6 g / cm 3 or more, and the batteries prepared therewith have excellent electrochemical performance.
[0007] According to the lithium iron phosphate positive electrode active material provided in the embodiment of the present disclosure, the particle size D mo The range of the discreteness of the particle size distribution A, as well as the range of the discreteness of the particle size distribution D for the two-component lithium iron phosphate material mo By defining the range of the relationship between A and A, it is ensured that a positive electrode sheet prepared with a positive electrode active material formed by mixing two lithium iron phosphate materials in any ratio has a high compressed density, and the compressed density is up to 2.6 g / cm 3 This promotes the improvement of the energy density of the battery prepared with the cathode active material. In addition, the battery prepared with the cathode active material has excellent electrochemical performance, especially good cycle performance.
[0008] In some embodiments, D 1 mo The value of D is 0.31≦D 1 mo ≦2.5.
[0009] In some embodiments, D 1 mo The value of D is 0.35≦D 1 mo ≦2.46.
[0010] In some embodiments, D 2 mo The value of D is 1.2≦D 2 mo ≦4.5.
[0011] In some embodiments, D 2 mo The value of D is 1.25≦D 2 mo ≦4.48.
[0012] In some embodiments, the mixing weight ratio of the first lithium iron phosphate material and the second lithium iron phosphate material is in the range of 1:(0.4-4).
[0013] In some embodiments, the mixing weight ratio of the first lithium iron phosphate material and the second lithium iron phosphate material is in the range of 1:(0.6-2.5).
[0014] In some embodiments, the mixing weight ratio of the first lithium iron phosphate material and the second lithium iron phosphate material is in the range of 1:(1 to 2.5).
[0015] In some embodiments, the first lithium iron phosphate material and the second lithium iron phosphate material have a carbon coating layer on a surface thereof.
[0016] In some embodiments, D 1 mo and A1 is 4.08≦A1×(2.31+D 1 mo )≦15.9.
[0017] In some embodiments, D 1 mo and A1 is 4.11≦A1×(2.31+D 1 mo )≦15.86.
[0018] In some embodiments, D 2 mo and A2 is -0.38≦A2×(D 2 mo -1.15)≦13.95.
[0019] According to the lithium iron phosphate positive electrode active material provided in the first aspect of the present disclosure, the positive electrode active material is formed by mixing two lithium iron phosphate materials that satisfy specific particle size parameter requirements in any ratio, and the positive electrode sheet prepared with the positive electrode active material has high compressed density, and the battery prepared therewith has good cycle performance and rate performance.
[0020] In a second aspect, the present disclosure provides a method for preparing a lithium iron phosphate active cathode material. The method includes the steps of: providing a first lithium iron phosphate material and a second lithium iron phosphate material; when the volume distribution percentage of the first lithium iron phosphate material reaches a maximum value, the corresponding particle size is D 1 mo μm, 0.3≦D 1 mo When the volume distribution percentage of the second lithium iron phosphate material reaches a maximum value, the corresponding particle size is D 2 mo μm, 1≦D 2 mo ≦5, D 1 mo <D 2 mo The first lithium iron phosphate material has a discrete degree of particle size distribution A1, and the second lithium iron phosphate material has a discrete degree of particle size distribution A2, where 1≦A1≦3 and 2≦A2≦4. D 1 mo and A1 is 4.07 <A1×(2.31+D 1 mo )<16. D 2 mo and A2 is -0.4 <A2×(D 2 mo −1.15)<14. The first lithium iron phosphate material and the second lithium iron phosphate material are mixed to obtain a lithium iron phosphate positive electrode active material.
[0021] In the method for preparing lithium iron phosphate positive active material, two lithium iron phosphate materials that meet the requirements of specific particle size parameters are mixed in any ratio to ensure that the resulting positive active material has high compaction density, and the battery prepared with the positive active material has good cycle performance and rate performance. The preparation method has a simple process, is easy to operate, and is therefore suitable for use in large-scale production.
[0022] In a third aspect, the present disclosure provides a lithium-ion battery comprising a positive electrode sheet comprising a lithium iron phosphate positive electrode active material according to the first aspect of the present disclosure or a lithium iron phosphate positive electrode active material prepared according to the method described in the second aspect of the present disclosure.
[0023] In some embodiments, the lithium-ion battery further includes a negative electrode sheet, as well as an electrolyte and a separator disposed between the positive and negative electrode sheets.
[0024] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on a surface of the positive electrode current collector.
[0025] In some embodiments, the active cathode material layer includes a lithium iron phosphate active cathode material, a binder, and a conductive agent.
[0026] In some embodiments, the positive electrode current collector comprises any one of aluminum foil, carbon coated aluminum foil, and perforated aluminum foil.
[0027] In some embodiments, the conductive agent comprises at least one of carbon nanotubes, graphene, carbon black, and carbon fibers.
[0028] In some embodiments, the maximum compressed density of the positive electrode sheet is 2.6 g / cm 3 Greater than.
[0029] Lithium-ion batteries using this positive electrode sheet have high energy density and excellent cycle performance. [Brief description of the drawings]
[0030] [Figure 1] 1 shows cycle performance curves of each pouch-type battery in Embodiments 1 to 5 and Comparative Examples 1 and 2 of the present disclosure. [Diagram 2]1 is a process flow chart of a method for preparing a lithium iron phosphate active cathode material according to an embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0031] The present disclosure provides a lithium iron phosphate cathode active material, a preparation method thereof, and a lithium-ion battery. By adjusting the particle size parameters of two component lithium iron phosphate materials, the cathode active material obtained by mixing the two materials in any ratio can have a high packed density, and the battery prepared therewith has excellent electrochemical performance.
[0032] In a first aspect, the present disclosure provides a lithium iron phosphate active cathode material. The lithium iron phosphate active cathode material is formed by mixing a first lithium iron phosphate material and a second lithium iron phosphate material. When the volume distribution percentage of the first lithium iron phosphate material reaches a maximum value, the corresponding particle size is D 1 mo μm, 0.3≦D 1 mo When the volume distribution percentage of the second lithium iron phosphate material reaches a maximum value, the corresponding particle size is D 2 mo μm, 1≦D 2 mo ≦5, D 1 mo <D 2 mo The first lithium iron phosphate material has a discrete degree of particle size distribution A1, and the second lithium iron phosphate material has a discrete degree of particle size distribution A2, where 1≦A1≦3 and 2≦A2≦4. D 1 mo and A1 is 4.07 <A1×(2.31+D 1 mo )<16. D 2 mo and A2 is -0.4 <A2×(D 2 mo -1.15)<14.
[0033] The maximum compression density of the positive electrode sheet containing the positive electrode active material is 2.6 g / cm 3 or more, and the batteries prepared therewith have excellent electrochemical performance.
[0034] According to the lithium iron phosphate positive electrode active material provided in the present disclosure, the particle size D mo range of the discreteness of particle size distribution A, and D of the two-component lithium iron phosphate material mo By defining the range of the relevant relational expression of A, it is possible to determine whether a positive electrode sheet prepared from a positive electrode active material formed by mixing two lithium iron phosphate materials in any ratio has a density of 2.6 g / cm. 3 It is ensured that the positive electrode active material has a high pressed density of 4.08 or more, which promotes the improvement of the energy density of the battery prepared with the positive electrode active material. In addition, the battery prepared with the positive electrode active material has excellent electrochemical performance, especially cycle performance. In some embodiments, 4.08≦A1×(2.31+D 1 mo )≦15.9. In some embodiments, A×(2.31+D 1 mo ) is in the range of 4.11 to 15.86.
[0035] In some embodiments, −0.38≦A×(D 2 mo -1.15)≦13.95.
[0036] In some embodiments, the D of the first lithium iron phosphate material 1 mo and the D of the second lithium iron phosphate material 2 mo The value of can be obtained from its respective laser particle size distribution diagram. In particular, the test equipment is a laser particle size analyzer (such as Malvern 3000). The test method can be found in GB / T 19077-2016 / ISO 13320:2009 Particle size analysis-Laser diffraction methods.
[0037] In some embodiments, the discreteness of the particle size distribution of the first lithium iron phosphate material is A1=(D 1 90 -D 1 10 ) / D 1 50 and the degree of discreteness of the particle size distribution of the second lithium iron phosphate material is A2=(D 2 90 -D 2 10 ) / D 2 50 and D 1 90 represents the corresponding particle size when the cumulative volume distribution percentage is 90% in the laser particle size distribution diagram of the first lithium iron phosphate material, and D 1 10 represents the corresponding particle size when the cumulative volume distribution percentage of the first lithium iron phosphate material is 10%, and D 1 50 represents the corresponding particle size when the cumulative volume distribution percentage of the first lithium iron phosphate material is 50%. A smaller A1 represents a smaller discreteness of the particle size distribution (or a narrower width of the particle size distribution) and a higher concentration of the particle size distribution of the first lithium iron phosphate material. Similarly, D 2 90 , D 2 10 , and D. 2 50 represent the corresponding particle sizes when the cumulative volume distribution percentages reach 90%, 10%, and 50%, respectively, in the laser particle size distribution diagram of the second lithium iron phosphate material. D 1 90 , D 1 10 , and D. 1 50 The value of D for the second lithium iron phosphate material 2 90 , D 2 10 , and D. 2 50can also be obtained from their laser particle size distribution diagrams. Test methods can be found in GB / T 19077-2016 / ISO 13320:2009 Particle size analysis-Laser diffraction methods.
[0038] In some embodiments, D 1 mo <D 2 mo The lithium iron phosphate material D 1 mo When D is small, the diffusion path of lithium ions is relatively short, and the prepared battery has good electrical performance. 2 mo When the particle size D is large, the compressed density of the positive electrode active material can be increased. mo Given that, the two lithium iron phosphate materials can be ensured to form a dense packing when they are uniformly mixed in any ratio, thereby increasing the compressed density of the cathode sheet prepared with the cathode active material prepared therewith without compromising the cycling performance of the battery.
[0039] In some embodiments, D 1 mo The value of D is 0.31≦D 1 mo ≦2.5. Furthermore, D 1 mo The value of D is 0.35≦D 1 mo ≦2.46.
[0040] In some embodiments, D 2 mo The value of D is 1.2≦D 2 mo ≦5. Furthermore, D 2 mo The value of D is 1.2≦D 2 mo≦4.5. 2 mo The value of D is 1.25≦D 2 mo ≦4.48.
[0041] D 1 mo and D. 2 mo The value of is within the above range, and D 1 mo <D 2 mo When the above requirements are met, the two lithium iron phosphate materials can fully ensure the high compression density of the positive electrode sheet and the good electrochemical performance of the battery.
[0042] In some embodiments, the mixing weight ratio of the first lithium iron phosphate material and the second lithium iron phosphate material can be any ratio, and the maximum compressed density of the positive electrode sheet prepared with the lithium iron phosphate positive electrode active material is high, and the cycle performance of the battery prepared therewith is good. In some embodiments, the mixing weight ratio of the first lithium iron phosphate material and the second lithium iron phosphate material is in the range of 1:(0.4-4), further in the range of 1:(0.6-2.5), for example in the range of 1:(1-2.5). In this case, the positive electrode active material formed by mixing the two lithium iron phosphate materials can sufficiently ensure the high compressed density of the electrode sheet and the good cycle performance of the battery.
[0043] In some embodiments, the first lithium iron phosphate material and the second lithium iron phosphate material may have a carbon coating layer on the surface, which can be obtained by grinding, spray drying and sintering the mixed slurry of a phosphorus source, an iron source, a lithium source and a carbon source in sequence. In the present disclosure, the specific preparation method of the two lithium iron phosphate materials is not limited. The presence of the carbon coating layer allows the first and second lithium iron phosphate materials to have good electrical conductivity and less side reaction with the electrolyte. The positive electrode active material obtained by mixing the two has good electrical conductivity and good cycle performance of the battery.
[0044] According to the lithium iron phosphate positive electrode active material provided in the first aspect of the present disclosure, the positive electrode active material is formed by mixing two lithium iron phosphate materials that satisfy specific particle size parameter requirements in any ratio, and the positive electrode sheet prepared with the positive electrode active material has high compressed density, and the battery prepared therewith has good cycle performance and rate performance.
[0045] In a second aspect, the present disclosure provides a method for preparing a lithium iron phosphate positive electrode active material. As shown in FIG. 2, the method includes the following steps: S101: A first lithium iron phosphate material and a second lithium iron phosphate material are provided. When the volume distribution percentage of the first lithium iron phosphate material reaches a maximum value, the corresponding particle size is D 1 mo μm, 0.3≦D 1 mo When the volume distribution percentage of the second lithium iron phosphate material reaches a maximum value, the corresponding particle size is D 2 mo μm, 1≦D 2 mo ≦5, D 1 mo <D 2 mo The first lithium iron phosphate material has a discrete degree of particle size distribution A1, and the second lithium iron phosphate material has a discrete degree of particle size distribution A2, where 1≦A1≦3 and 2≦A2≦4. D 1 mo and A1 is 4.07 <A1×(2.31+D 1 mo )<16. D 2 mo and A2 is -0.4 <A2×(D 2 mo −1.15)<14. S102: The first lithium iron phosphate material and the second lithium iron phosphate material are mixed to obtain a lithium iron phosphate positive electrode active material.
[0046] In the method for preparing lithium iron phosphate positive active material, two lithium iron phosphate materials that meet the requirements of specific particle size parameters are mixed in any ratio to ensure that the resulting positive active material has high compaction density, and the battery prepared with the positive active material has good cycle performance and rate performance. The preparation method has a simple process, is easy to operate, and is therefore suitable for use in large-scale production.
[0047] A positive electrode sheet is provided, the positive electrode sheet comprising the lithium iron phosphate positive electrode active material according to the first aspect of the present disclosure or the lithium iron phosphate positive electrode active material prepared according to the method described in the second aspect of the present disclosure.
[0048] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on a surface of the positive electrode current collector. The positive electrode active material layer includes a lithium iron phosphate positive electrode active material, a binder, and a conductive agent.
[0049] In some embodiments, the maximum compressed density of the positive electrode sheet is 2.6 g / cm 3 In some embodiments, the maximum compressed density is 2.62 to 2.8 g / cm 3 , and even 2.65 to 2.75 g / cm 3 It should be understood that the maximum compressed density of the positive electrode sheet refers to the corresponding compressed density of the electrode sheet when the active material particles in the positive electrode sheet are crushed under a certain pressure.
[0050] The positive electrode material layer can be formed by coating a positive electrode paste including a lithium iron phosphate positive electrode active material, a conductive agent, a binder, and a solvent on a positive electrode current collector. The solvent may be one or more of N-methylpyrrolidone (NMP), acetone, and dimethylacetamide (DMAC). The positive electrode current collector includes any one of aluminum foil, carbon-coated aluminum foil, and perforated aluminum foil. The conductive agent includes, but is not limited to, one or more of carbon nanotubes, graphene, carbon black, carbon fiber, and the like. The binder includes, but is not limited to, one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA), styrene-butadiene rubber (SBR), polyacrylic acid (PAA), polyacrylate, polyacrylonitrile (PAN), sodium carboxymethyl cellulose (CMC), and sodium alginate.
[0051] In a third aspect, the present disclosure provides a lithium-ion battery comprising a positive electrode sheet according to the third aspect of the present disclosure.
[0052] In some embodiments, the lithium-ion battery further includes a negative electrode sheet, as well as an electrolyte and a separator disposed between the positive and negative electrode sheets.
[0053] Lithium-ion batteries using this positive electrode sheet have high energy density and excellent cycle performance.
[0054] The following description is some implementation forms of the present disclosure. It should be noted that without departing from the principle of the present disclosure, multiple improvements and modifications can be made by those skilled in the art, which shall fall within the protection scope of the present disclosure.
[0055] Hereinafter, the technical solutions of the present disclosure will be described in combination with specific embodiments.
[0056] Illustrative Example 1
[0057] The method for preparing the lithium iron phosphate active cathode material (hereinafter referred to as the active cathode material) includes the following steps.
[0058] The first lithium iron phosphate material LFP-1 was used. When the volume distribution percentage of LFP-1 reached the maximum value, the corresponding particle size was 0.31 μm, and the discreteness of the particle size distribution was 2.22. That is, D 1 mo is 0.31, A1 is 2.22, and A1×(2.31+D 1 mo )=5.82. A second lithium iron phosphate material, LFP-2, was used. When the volume distribution percentage of LFP-2 reached a maximum value, the corresponding particle size was 1.28 μm, and the discreteness of the particle size distribution was 2.24. That is, D 2 mo is 1.28, A2 is 2.24, and A2 × (D 2 mo -1.15)=0.29.
[0059] The LFP-1 and LFP-2 materials were mixed in a weight ratio of 2:8 to obtain the lithium iron phosphate positive electrode active material LFP-3.
[0060] The lithium iron phosphate cathode active material LFP-3 was prepared into a cathode sheet as follows: the LFP-3 material was mixed with a conductive agent, i.e., carbon nanotubes, a binder, specifically polyvinylidene fluoride (PVDF), and a solvent, N-methylpyrrolidone (NMP), in a weight ratio of 100:3:2:60 and mixed uniformly to obtain a cathode paste. The cathode paste was coated on both sides of a carbon-coated aluminum foil and dried to obtain a cathode sheet with a thickness of 360 g / m2. 2 A double-sided positive electrode sheet with an areal density of 2.70 g / cm was obtained. The maximum compressed density of the positive electrode sheet without particle breakage was determined. 3 It was.
[0061] Preparation of pouch-type lithium-ion battery. A negative plate was prepared by coating a mixed paste containing graphite:conductive agent (carbon black):binder (specifically SBR):water = 100:2:5:120 (weight ratio) on copper foil and drying it to provide a negative plate. A positive electrode sheet prepared with the positive electrode active material LFP-3 in Example 1 was used as the positive electrode. A polypropylene film was used as the separator. A solution containing 1.0 mol / L LiPF6 in ethylene carbonate (EC): dimethyl carbonate (DMC) = 1:1 (volume ratio) was used as the electrolyte. After assembly, a pouch-type lithium-ion battery was obtained.
[0062] Illustrative Example 2
[0063] The method for preparing the lithium iron phosphate positive electrode active material was different from that in Example 1 in that the LFP-1 material and the LFP-2 material were mixed in a weight ratio of 4:6. The other steps were the same as those in Example 1. The lithium iron phosphate positive electrode active material LFP-3 was obtained.
[0064] According to the method described in Example 1, the lithium iron phosphate positive active material LFP-3 obtained in Example 2 was prepared into a positive electrode sheet and assembled into a pouch-type lithium-ion battery. The maximum compressed density of the positive electrode sheet in Example 2 was 2.68 g / cm. 3 It was determined that.
[0065] Illustrative Example 3
[0066] The method for preparing the lithium iron phosphate positive electrode active material includes the following steps.
[0067] The first lithium iron phosphate material LFP-1 was used. When the volume distribution percentage of LFP-1 reached the maximum value, the corresponding particle size was 3.12 μm, and the discreteness of the particle size distribution was 2.92. That is, D 1 mo is 3.12, A1 is 2.92, and A1×(2.31+D 1mo )=15.86. A second lithium iron phosphate material, LFP-2, was used. When the volume distribution percentage of LFP-2 reached a maximum value, the corresponding particle size was 4.93 μm, and the discreteness of the particle size distribution was 3.69. That is, D 2 mo is 4.93, A2 is 3.69, and A2×(D 2 mo -1.15)=13.95.
[0068] The LFP-1 and LFP-2 materials were mixed in a weight ratio of 5:5 to obtain the lithium iron phosphate cathode active material LFP-3.
[0069] According to the method described in Example 1, the lithium iron phosphate positive active material LFP-3 obtained in Example 3 was prepared into a positive electrode sheet and assembled into a pouch-type lithium-ion battery. The maximum compressed density of the positive electrode sheet in Example 3 was 2.73 g / cm. 3 It was determined that.
[0070] Illustrative Example 4
[0071] The method for preparing the lithium iron phosphate positive electrode active material includes the following steps.
[0072] The first lithium iron phosphate material LFP-1 was used. When the volume distribution percentage of LFP-1 reached the maximum value, the corresponding particle size was 1.41 μm, and the discreteness of the particle size distribution was 2.32. That is, D 1 mo is 1.41, A1 is 2.32, and A1×(2.31+D 1 mo )=8.63. A second lithium iron phosphate material, LFP-2, was used. When the volume distribution percentage of LFP-2 reached a maximum value, the corresponding particle size was 3.36 μm, and the discreteness of the particle size distribution was 2.58. That is, D 2 mo is 3.36, A2 is 2.58, and A2×(D 2 mo-1.15)=5.70.
[0073] The LFP-1 and LFP-2 materials were mixed in a weight ratio of 3:7 to obtain the lithium iron phosphate cathode active material LFP-3.
[0074] According to the method described in Example 1, the lithium iron phosphate positive active material LFP-3 obtained in Example 4 was prepared into a positive electrode sheet and assembled into a pouch-type lithium-ion battery. The maximum compressed density of the positive electrode sheet in Example 4 was 2.68 g / cm. 3 It was determined that.
[0075] Illustrative Example 5
[0076] The method for preparing the lithium iron phosphate positive electrode active material includes the following steps.
[0077] The first lithium iron phosphate material LFP-1 was used. When the volume distribution percentage reached the maximum value, the corresponding particle size was 2.46 μm, and the discreteness of the particle size distribution was 2.16. That is, D 1 mo is 2.46, A1 is 2.16, and A1×(2.31+D 1 mo ) = 10.30. A second lithium iron phosphate material, LFP-2, was used. When the volume distribution percentage reached a maximum value, the corresponding particle size was 4.48 μm, and the discreteness of the particle size distribution was 3.92. That is, D 2 mo is 4.48 μm, A2 is 3.92, and A2 × (D 2 mo -1.15)=13.05.
[0078] The LFP-1 and LFP-2 materials were mixed in a weight ratio of 7:3 to obtain lithium iron phosphate positive electrode active material LFP-3.
[0079] According to the method described in Example 1, the lithium iron phosphate positive active material LFP-3 obtained in Example 5 was prepared into a positive electrode sheet and assembled into a pouch-type lithium-ion battery. The maximum compressed density of the positive electrode sheet in Example 5 was 2.65 g / cm 3 It was determined that.
[0080] Illustrative Example 6
[0081] The method for preparing the lithium iron phosphate positive electrode active material includes the following steps.
[0082] The first lithium iron phosphate material LFP-1 was used. When the volume distribution percentage reached the maximum value, the corresponding particle size was 0.8 μm, and the discreteness of the particle size distribution was 1.32. That is, D 1 mo is 0.8, A1 is 1.32, and A1×(2.31+D 1 mo ) = 4.11. A second lithium iron phosphate material, LFP-2, was used. When the volume distribution percentage reached a maximum value, the corresponding particle size was 1.65 μm, and the degree of discreteness of the particle size distribution was 3.6. That is, D 2 mo is 1.65, A2 is 3.6, and A2 × (D 2 mo -1.15)=1.8.
[0083] The LFP-1 and LFP-2 materials were mixed in a weight ratio of 3:7 to obtain the lithium iron phosphate cathode active material LFP-3.
[0084] According to the method described in Example 1, the lithium iron phosphate positive active material LFP-3 obtained in Example 6 was prepared into a positive electrode sheet and assembled into a pouch-type lithium-ion battery. The maximum compressed density of the positive electrode sheet in Example 6 was 2.66 g / cm. 3 It was determined that.
[0085] Illustrative Example 7
[0086] The method for preparing the lithium iron phosphate positive electrode active material includes the following steps.
[0087] The first lithium iron phosphate material LFP-1 was used. When the volume distribution percentage reached the maximum value, the corresponding particle size was 0.64 μm, and the discreteness of the particle size distribution was 2.8. That is, D 1 mo is 0.64, A1 is 2.8, and A1×(2.31+D 1 mo )=8.26. A second lithium iron phosphate material, LFP-2, was used. When the volume distribution percentage reached a maximum value, the corresponding particle size was 1.02 μm, and the discreteness of the particle size distribution was 2.94. That is, D 2 mo is 1.02, A2 is 2.94, and A2 × (D 2 mo -1.15) = -0.38.
[0088] The LFP-1 and LFP-2 materials were mixed in a weight ratio of 6:4 to obtain the lithium iron phosphate positive electrode active material LFP-3.
[0089] According to the method described in Example 1, the lithium iron phosphate positive active material LFP-3 obtained in Example 7 was prepared into a positive electrode sheet and assembled into a pouch-type lithium-ion battery. The maximum compressed density of the positive electrode sheet in Example 7 was 2.65 g / cm. 3 It was determined that.
[0090] To highlight the beneficial effects of the present disclosure, the following Comparative Examples 1 to 6 are provided.
[0091] Illustrative Comparative Example 1
[0092] The method for preparing the lithium iron phosphate positive electrode active material includes the following steps.
[0093] The first lithium iron phosphate material LFP-1 was used. When the volume distribution percentage reached a maximum value, the corresponding particle size was 0.35 μm (i.e., D 1 mo was 0.35), and the degree of discreteness A1 of the particle size distribution was 1.27, but A1 × (2.31 + D 1 mo )=3.38, which is outside the range of (4.07,16) specified in this disclosure. A second lithium iron phosphate material, LFP-2, was used. When the volume distribution percentage reached a maximum value, the corresponding particle size was 1.03 μm (i.e., D 2 mo was 1.03), and the degree of discreteness A2 of the particle size distribution was 3.87, but A2 × (D 2 mo -1.15) = -0.46, which was outside the range of (-0.4, 14) specified in this disclosure.
[0094] The LFP-1 and LFP-2 materials were mixed in a weight ratio of 1:1 to obtain the lithium iron phosphate cathode active material LFP-3.
[0095] According to the method described in Example 1, the lithium iron phosphate positive active material LFP-3 obtained in Comparative Example 1 was prepared into a positive electrode sheet and assembled into a pouch-type lithium-ion battery. The maximum compressed density of the positive electrode sheet in Comparative Example 1 was 2.58 g / cm. 3 It was determined that.
[0096] Illustrative Comparative Example 2
[0097] A lithium iron phosphate positive electrode material was provided in which only one lithium iron phosphate material was used as the positive electrode active material. When the volume distribution percentage reached a maximum value, the corresponding particle size was 0.31 μm, and the discreteness A of the particle size distribution was 1.92.
[0098] According to the method described in Example 1, the lithium iron phosphate positive electrode material obtained in Comparative Example 2 was prepared into a positive electrode sheet and assembled into a pouch-type lithium-ion battery. The maximum compressed density of the pouch-type battery was 2.55 g / cm. 3 It was.
[0099] Illustrative Comparative Example 3
[0100] The method for preparing the lithium iron phosphate positive electrode active material includes the following steps.
[0101] The first lithium iron phosphate material LFP-1 was used. When the volume distribution percentage reached a maximum value, the corresponding particle size was 0.35 μm (i.e., D 1 mo was 0.35), and the degree of discreteness A1 of the particle size distribution was 1.24, but A1 × (2.31 + D 1 mo )=3.30, which is outside the range of (4.07,16) specified in this disclosure. A second lithium iron phosphate material, LFP-2, was used. When the volume distribution percentage reached a maximum value, the corresponding particle size was 5.11 μm (i.e., D 2 mo is 5.11), which is outside the range of (1,5) specified in this disclosure, and the degree of discreteness A2 of the particle size distribution is 3.78, and A2 × (D 2 mo -1.15)=14.97, which was outside the range of (-0.4, 14) specified in this disclosure.
[0102] The LFP-1 and LFP-2 materials were mixed in a weight ratio of 2:8 to obtain the lithium iron phosphate cathode active material LFP-3.
[0103] According to the method described in Example 1, the positive electrode active material LFP-3 obtained in Comparative Example 3 was prepared into a positive electrode sheet and assembled into a pouch-type battery. The maximum compressed density of the positive electrode sheet in Comparative Example 3 was 2.63 g / cm 3 It was determined that the maximum compressed density of the positive electrode sheet in Comparative Example 3 was 2.6 g / cm3 As shown in Table 1 below, the first cycle coulombic efficiency, first cycle discharge specific capacity, and capacity retention rate after 1000 cycles of the battery having the positive electrode sheet in Comparative Example 3 were lower than those in Example 1.
[0104] Comparative Illustrative Example 4
[0105] The method for preparing the lithium iron phosphate positive electrode active material includes the following steps.
[0106] The first lithium iron phosphate material LFP-1 was used. When the volume distribution percentage reached a maximum value, the corresponding particle size was 0.46 μm (i.e., D 1 mo was 0.46), and the degree of discreteness A1 of the particle size distribution was 1.22, but A1 × (2.31 + D 1 mo )=3.38, which is outside the range of (4.07,16) specified in this disclosure. A second lithium iron phosphate material, LFP-2, was used. When the volume distribution percentage reached a maximum value, the corresponding particle size was 1.47 μm (i.e., D 2 mo is 1.47), the degree of discreteness A2 of the particle size distribution is 2.66, and A2 × (D 2 mo -1.15) = 0.85, which was within the range of (-0.4, 14) specified in this disclosure.
[0107] The LFP-1 and LFP-2 materials were mixed in a weight ratio of 3:7 to obtain the lithium iron phosphate cathode active material LFP-3.
[0108] According to the method described in Example 1, the lithium iron phosphate positive active material LFP-3 obtained in Comparative Example 4 was prepared into a positive electrode sheet and assembled into a pouch-type lithium-ion battery. The maximum compressed density of the positive electrode sheet in Comparative Example 4 was only 2.57 g / cm 3 It was determined that.
[0109] Comparative Illustrative Example 5
[0110] The method for preparing the lithium iron phosphate positive electrode active material includes the following steps.
[0111] The first lithium iron phosphate material LFP-1 was used. When the volume distribution percentage reached a maximum value, the corresponding particle size was 3.1 μm (i.e., D 1 mo is 3.1), which is within the range of 0.3 to 3.2 μm specified in this disclosure, and the degree of discreteness A1 of the particle size distribution is 2.58, and A1 × (2.31 + D 1 mo )=13.96. A second lithium iron phosphate material, LFP-2, was used. When the volume distribution percentage reached a maximum value, the corresponding particle size was 5.23 μm (i.e., D 2 mo is 5.23), which is outside the range of (1,5) specified in this disclosure, and the degree of discreteness A2 of the particle size distribution is 3.29, and A2 × (D 2 mo -1.15) = 13.42, which was within the range of (-0.4, 14) specified in this disclosure.
[0112] The LFP-1 and LFP-2 materials were mixed in a weight ratio of 5:5 to obtain the lithium iron phosphate cathode active material LFP-3.
[0113] According to the method described in Example 1, the lithium iron phosphate positive active material LFP-3 obtained in Comparative Example 5 was prepared into a positive electrode sheet and assembled into a pouch-type lithium-ion battery. The maximum compressed density of the positive electrode sheet in Comparative Example 5 was 2.62 g / cm 3 It was determined that the maximum compressed density of the positive electrode sheet in Comparative Example 5 was 2.6 g / cm 3As shown in Table 1 below, the first cycle coulombic efficiency, first cycle discharge specific capacity, and capacity retention rate after 1000 cycles of the battery having the positive electrode sheet in Comparative Example 5 were lower than those in Example 1.
[0114] Comparative Illustrative Example 6
[0115] The method for preparing the lithium iron phosphate positive electrode active material includes the following steps.
[0116] The first lithium iron phosphate material LFP-1 was used. When the volume distribution percentage reached a maximum value, the corresponding particle size was 0.54 μm (i.e., D 1 mo is 0.54), the degree of discreteness A1 of the particle size distribution is 1.87, and A1 × (2.31 + D 1 mo )=5.33. A second lithium iron phosphate material, LFP-2, was used. When the volume distribution percentage reached a maximum value, the corresponding particle size was 1.12 μm (i.e., D 2 mo is 1.12), the degree of discreteness A2 of the particle size distribution is 1.61, which is outside the range of 2 to 4 specified in this disclosure, and A2 × (D 2 mo-1.15)=-0.05.
[0117] The LFP-1 and LFP-2 materials were mixed in a weight ratio of 6:4 to obtain the lithium iron phosphate positive electrode active material LFP-3.
[0118] According to the method described in Example 1, the lithium iron phosphate positive active material LFP-3 obtained in Comparative Example 6 was prepared into a positive electrode sheet and assembled into a pouch-type lithium-ion battery. The maximum compressed density of the positive electrode sheet in Comparative Example 6 was 2.54 g / cm. 3 It was determined that.
[0119] To provide strong support for the beneficial effects of the present disclosure, the cycle performance of the pouch-type batteries of each Example and Comparative Example was tested. Each pouch-type battery was subjected to a charge-discharge cycle test at 0.5C / 0.5C and 25°C. The voltage range was 2.0-3.8V. Figure 1 shows the cycle performance curves of each pouch-type battery in Examples 1-5 and Comparative Examples 1-2. The first cycle coulombic efficiency, first cycle discharge specific capacity, and capacity retention after 1000 cycles of the batteries in the Examples and Comparative Examples are summarized in Table 1 below. [Table 1]
[0120] As can be seen from FIG. 1 and Table 1, in Comparative Example 2, in which only one lithium iron phosphate material was used as the positive electrode active material, the charge-discharge cycle performance of the battery was good, but the maximum compressed density of the electrode sheet was low, which was not conducive to improving the energy density of the battery. When the two lithium iron phosphate materials were mixed by the method provided in the present disclosure, the compressed density of the positive electrode sheet prepared with the positive electrode active material was high, 2.6 g / cm. 3 More than this, and in some cases 2.65 to 2.75 g / cm 3 In addition, the battery has excellent electrochemical performance, high first cycle discharge specific capacity, and high first cycle Coulombic efficiency, and the cycling performance (Examples 1-7) is comparable to that of the low packed density battery in Comparative Example 2. However, when a positive electrode active material obtained by mixing two raw materials that do not meet the specific requirements in the present disclosure is used (Comparative Examples 1, and 3-6), the packed density of the electrode sheet is too low, for example, in Comparative Examples 1-2, 4, and 6, or the packed density is sometimes as low as 2.6 g / cm3, for example, in Comparative Examples 3 and 5. 3 or more, but the charge-discharge cycle stability is poor. Generally, high packing density and good cycle performance of the electrode sheet cannot be realized simultaneously.
[0121] The above embodiments only show and describe several implementation forms of the present disclosure, but they should not be interpreted as limitations on the scope of the present disclosure. It should be understood by those skilled in the art that several modifications and improvements can be made by those skilled in the art without departing from the concept of the present disclosure, all of which are envisaged within the scope of protection of the present disclosure. Therefore, the scope of protection of the present disclosure shall be defined by the appended claims.
Claims
1. a lithium iron phosphate positive electrode active material formed by mixing a first lithium iron phosphate material and a second lithium iron phosphate material, When the volume distribution percentage of the first lithium iron phosphate material reaches a maximum value, the corresponding particle size is D 1 mo μm, and 0.3≦D 1 mo ≦3.2, and when the volume distribution percentage of the second lithium iron phosphate material reaches a maximum value, the corresponding particle size is D 2 mo μm, 1≦D 2 mo ≦5, D 1 mo <D 2 mo and The degree of discreteness of the particle size distribution of the first lithium iron phosphate material is A 1 and the degree of discreteness of the particle size distribution of the second lithium iron phosphate material is A 2 where 1≦A 1 ≦3, and 2≦A 2 ≦4, D 1 mo and A 1 is 4.07<A 1 × (2.31 + D 1 mo ) < 16, and D 2 mo and A 2 is -0.4 < A 2 × (D 2 mo -1.15) < 14. Lithium iron phosphate positive electrode active material.
2. D 1 mo The value of D is 0.31≦D 1 mo 2. The lithium iron phosphate positive electrode active material of claim 1, wherein the .alpha.-methyl-2.5 carbon atom is in the range of .lambda..
3. D 1 mo The value of D is 0.35≦D 1 mo 3. The lithium iron phosphate positive electrode active material according to claim 1, wherein the σ is in the range of ≦2.
46.
4. D 2 mo The value of D is 1.2≦D 2 mo 4. The lithium iron phosphate positive electrode active material according to claim 1 , wherein the β-
5. D 2 mo The value of D is 1.25≦D 2 mo 5. The lithium iron phosphate positive electrode active material according to claim 1 , wherein the σ is in the range of ≦4.
48.
6. The lithium iron phosphate positive electrode active material according to any one of claims 1 to 5, wherein the mixing weight ratio of the first lithium iron phosphate material and the second lithium iron phosphate material is in the range of 1: (0.4 to 4).
7. 7. The lithium iron phosphate positive electrode active material according to claim 1, wherein the mixing weight ratio of the first lithium iron phosphate material and the second lithium iron phosphate material is in the range of 1:(0.6 to 2.5).
8. The lithium iron phosphate positive electrode active material according to any one of claims 1 to 7, wherein the mixing weight ratio of the first lithium iron phosphate material and the second lithium iron phosphate material is in the range of 1: (1 to 2.5).
9. 9. The lithium iron phosphate positive electrode active material of claim 1, wherein the first lithium iron phosphate material and the second lithium iron phosphate material have a carbon coating layer on a surface thereof.
10. D 1 mo and A 1 4.08≦A 1 × (2.31 + D 1 mo 10. The lithium iron phosphate positive electrode active material according to claim 1 , wherein the lithium iron phosphate positive electrode active material satisfies the relationship:
11. D 1 mo and A 1 4.11≦A 1 × (2.31 + D 1 mo 11. The lithium iron phosphate positive electrode active material according to claim 1 , wherein the lithium iron phosphate positive electrode active material satisfies the relationship:
12. D 2 mo and A 2 is -0.38≦A 2 × (D 2 mo The lithium iron phosphate positive electrode active material according to any one of claims 1 to 11, wherein the lithium iron phosphate positive electrode active material satisfies the relationship: -1.15)≦13.
95.
13. 1. A method for preparing a lithium iron phosphate positive electrode active material, comprising: (S101) Providing a first lithium iron phosphate material and a second lithium iron phosphate material, wherein when the volume distribution percentage of the first lithium iron phosphate material reaches a maximum value, the corresponding particle size is D 1 mo μm, and 0.3≦D 1 mo ≦3.2, and when the volume distribution percentage of the second lithium iron phosphate material reaches a maximum value, the corresponding particle size is D 2 mo μm, 1≦D 2 mo ≦5, D 1 mo <D 2 mo and the degree of discreteness of the particle size distribution of the first lithium iron phosphate material is A 1 and the degree of discreteness of the particle size distribution of the second lithium iron phosphate material is A 2 where 1≦A 1 ≦3, and 2≦A 2 ≦4, D 1 mo and A 1 is 4.07<A 1 × (2.31 + D 1 mo ) < 16, and D 2 mo and A 2 is -0.4 < A 2 × (D 2 mo -1.15) < 14, and providing (S102) mixing the first lithium iron phosphate material and the second lithium iron phosphate material to obtain the lithium iron phosphate positive electrode active material; A method for preparing a lithium iron phosphate positive electrode active material comprising:
14. 14. A lithium ion battery comprising a positive electrode sheet, the positive electrode sheet comprising the lithium iron phosphate positive electrode active material according to any one of claims 1 to 12, or the positive electrode sheet comprising the lithium iron phosphate positive electrode active material prepared by the method for preparing the lithium iron phosphate positive electrode active material according to claim 13.
15. 15. The lithium ion battery of claim 14, further comprising a negative electrode sheet, and an electrolyte and a separator disposed between the positive and negative electrode sheets.
16. 16. The lithium ion battery of claim 14 or 15, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on a surface of the positive electrode current collector.
17. 17. The lithium ion battery of claim 16, wherein the active cathode material layer comprises the lithium iron phosphate active cathode material, a binder, and a conductive agent.
18. 18. The lithium ion battery of claim 16 or 17, wherein the positive electrode current collector comprises one of aluminum foil, carbon coated aluminum foil, and perforated aluminum foil.
19. 19. The lithium ion battery of claim 17 or 18, wherein the conductive agent comprises at least one of carbon nanotubes, graphene, carbon black, and carbon fibers.
20. The maximum compressed density of the positive electrode sheet is 2.6 g / cm 3 20. The lithium ion battery of claim 14, wherein the capacitance is greater than 1.
Citation Information
Patent Citations
Cathode active material, cathode plate and electrochemical device
CN110970602A
Lithium iron phosphate positive electrode material as well as preparation method and application thereof
CN113800493A
Positive electrode active material for secondary battery, and secondary battery
WO2020162277A1